Rates of very preterm birth in Europe and neonatal mortality rates. Issue 4 (9th December 2008) - Field, D; Draper, E S; Fenton, A; Papiernik, E; Zeitlin, J; Blondel, B; Cuttini, M; Maier, R F; Weber, T; Carrapato, M; Kollée, L; Gadzin, J; et al.
Abstract : Objective: To estimate the influence of variation in the rate of very preterm delivery on the reported rate of neonatal death in 10 European regions. Design: Comparison of 10 separate geographically defined European populations, from nine European countries, over a 1-year period (7 months in one region). Participants: All births that occurred between 22 +0 and 31 +6 weeks of gestation in 2003. Main outcome measure: Neonatal death rate adjusted for rate of delivery at this gestation. Results: Rate of delivery of all births at 22 +0 –31 +6 weeks of gestation and live births only were calculated for each region. Two regions had significantly higher rates of very preterm delivery per 1000 births: Trent UK (16.8, 95% CI 15.7 to 17.9) and Northern UK (17.1, 95% CI 15.6 to 18.6); group mean 13.2 (95% CI 12.9 to 13.5). Four regions had rates significantly below the group average: Portugal North (10.7, 95% CI 9.6 to 11.8), Eastern and Central Netherlands (10.6, 95% CI 9.7 to 11.6), Eastern Denmark (11.2, 95% CI 10.1 to 12.4) and Lazio in Italy (11.0, 95% CI 10.1 to 11.9). Similar trends were seen in live birth data. Published rates of neonatal death for each region were then adjusted by applying (a) a standardised rate of very preterm delivery and (b) the existing death rate for babies born at this gestation in the individual region. This produced much greater homogeneity in terms of neonatal mortality. Conclusions: Variation in the rate of very preterm delivery has a major influence on reported neonatal death rates.